The Impact of Heat Stress on Physiological Health in Industrial Workers: A Mixed-Methods Study - Imam Munajat Nurhartonosuro; Shamsul Bahri Md Tamrin; Dayana Hazwani Mohd Suadi Nata; Karmegam Karuppiah; Ng Yee Guan; Gede Pramudya Ananta (The Indonesian Journal of Occupational Safety and Health, 2025)
Introduction: The discrepancy between actual heat stress and workers' perception results in a mitigation failure, potentially leading to fatality. This study aimed to investigate workplace heat stress, workers' workload, and personnel's heat strain in steel mills under extreme temperature conditions. Methods: The study used a mixed-methods design and was conducted across three steel mills in East Java, Indonesia. An analysis of heat-stress data included heat-stress symptoms derived from physiological and environmental factors, while the personal perception assessment was based on comprehensive interview sessions. These quantitative results, obtained from 119 operators, were compared with workers' personal thermal perceptions using a mixed-methods approach. Phase 1 quantitative method consisted of onsite data collection, walkthrough inspection, questionnaire distribution, workplace monitoring, personal assessment, and statistical analysis. Phase 2, as a qualitative stage, consisted of in-depth interviews and focused group discussions with 15 participants. Results: The wet-bulb globe temperature measurements confirm significant heat stress in all mills. Workers' physiological responses remained within acceptable limits according to ACGIH criteria. However, a noticeable discrepancy was found between the quantitative data and workers' perceptions, highlighting the need for greater awareness and training on heat-stress hazards. Conclusion: The alignment between qualitative and quantitative findings underscores the importance of integrating both approaches to develop effective mitigation strategies. This study contributes to understanding occupational heat stress in high-risk environments and emphasizes the need to incorporate worker perceptions into health and safety protocols.